2018
DOI: 10.1128/aac.00797-18
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin Treatment of Candida albicans Biofilms Enhances Neutrophil Extracellular Trap Formation

Abstract: The nosocomial pathogen forms biofilms on medical devices that persist in the face of antifungals and host defenses. Echinocandins, the most effective antibiofilm drugs, have recently been shown to augment the activity of neutrophils against biofilms through an unknown mechanism. Here, we show that treatment of biofilms with subinhibitory concentrations of echinocandins promotes the formation of neutrophil extracellular traps (NETs), structures of DNA, histones, and antimicrobial proteins with antifungal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Activation of NETosis in contact with fungal biofilm exposing eRNA/eDNA in ECM could also be supported by the antifungal treatment, such as with echinocandins. By influencing the fungal cell organization, it can augment the innate immune response of the host ( Hoyer et al., 2018 ). A better understanding of fungal biofilm formation, composition and stability during infection progression will open new avenues for the development of effective antifungal therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NETosis in contact with fungal biofilm exposing eRNA/eDNA in ECM could also be supported by the antifungal treatment, such as with echinocandins. By influencing the fungal cell organization, it can augment the innate immune response of the host ( Hoyer et al., 2018 ). A better understanding of fungal biofilm formation, composition and stability during infection progression will open new avenues for the development of effective antifungal therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal components involved in triggering this response are not certain. The finding that neutrophils are also activated by biofilms following treatment with echinocandin drugs, which unmask β-1,3 glucan, suggests a role for this polysaccharide (Katragkou et al, 2010;Hoyer et al, 2018;Simitsopoulou et al, 2018).…”
Section: Role Of Candida Biofilm Matrix In Immunitymentioning
confidence: 99%
“…may vary in morphology and density, the structures uniformly contain a polymeric extracellular matrix that encases and protects the fungal cells. The components of the extracellular matrix differ from those found in the Candida cell wall, and these moieties are proposed to modulate host recognition by concealing the cell wall components that typically interact with the immune system (Johnson et al, 2016;Zawrotniak et al, 2017;Hoyer et al, 2018). In addition, cells dispersed from biofilms exhibit characteristics distinct from cells growing under non-biofilm conditions (Sellam et al, 2009;Uppuluri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hoyer et al. ( 56 ) reported that C. albicans biofilms treated with appropriate concentrations of echinocandin unexpectedly stimulated the formation of NETs. In summary, although some elements of biofilms were found to trigger NET formation, the inhibitory action exhibited by biofilms as a whole has been confirmed.…”
Section: Multiple Virulence Factors Of C Albicans ...mentioning
confidence: 99%